Implementasi Sistem Informasi Penerimaan Siswa Baru Pada SMK / SMA Yapim Taruna Marelan Berbasis Web - Randi Rian Putra (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
PSB is one of the administrative processes that will be used by prospective students every year. Acceptance of prospective students is based on the criteria obtained when graduating from SMP / MA, Prospective students referred to are new students who will register at the SMK / SMA level. The problem is that prospective students from outside the area also find it difficult to register because they have to go to school first, where it is very time-consuming and requires a lot of money. In research and system testing, it is carried out with several methods, namely field research, library research and laboratory research. Field research was carried out by direct observation to SMK / SMA Yapim Taruna Marelan, so that the working mechanism of the existing system was known. Literature research is done by studying books that can add to the study of science for this system and research. Whereas laboratory research is carried out by creating a web-based PSB. The benefits of this research can improve the quality of SMK / SMA Yapim Taruna Marelan in the admission of new students and the increasing number of students each year. Keywords: acceptance of new students, psb